PORTOFOLIO VIDEO SEBAGAI SEBUAH BENTUK PENILAIAN ALTERNATIF KEMAMPUAN BERBICARA BAHASA INGGRIS - A. Fitria Hanim (Universitas Tanjungpura, 2022)
This study aimed at describing and examining the uses and benefits of video portfolio in assessing the English speaking ability of grade IX students of SMP Negeri 1 Sintang. The research design used was a qualitative description. Data collection techniques used were observation, interviews, and documentation. The data analysis technique used was descriptive qualitative method because the data obtained were in the form of field notes and interviews. The results of the study showed that the use of video portfolio in the assessment of English speaking skill passed through several stages carried out from the process of action preparation, implementation of actions to the stage of assessing students’ performance results. The use of video portfolio in the assessment of the English speaking ability of grade IX students of SMP Negeri 1 Sintang provided many benefits so that it could be one of the solutions in assessing English speaking skill.